Molecular Imaging for Integrated Medical Therapy and Drug Development - Tamaki, Nagara; Kuge, Yuji.; SpringerLink (Online service) (Tokyo : Springer Japan, 2010)
Molecular imaging plays an important role in drug discovery and advanced medical practice. A symposium of world leaders in drug research and development, molecular imaging, and medical therapy including regenerative treatment and radiation therapy has led to the publication of this book. Based on the proceedings of the symposium, many excellent ideas and valuable discussions are introduced that will guide the reader toward new advances in photon detection and protein modification as well as new developments in molecular imaging itself. Both protein modification and photon detection are emerging technologies that hold forth the promise of innovative strategies for drug discovery and medical care. The publication of these proceedings is a timely means of sharing significant experience and knowledge with many specialists all over the world. This book will be of great value to a wide variety of researchers in the fields of drug development and molecular imaging technologies, leading to integrated medical therapy and progress in human health.
Advances in Molecular Imaging -- Advances in Molecular Imaging -- New Molecular Imaging and Image-Guided Radiotherapy -- Hypoxia Imaging for Image-Guided Radiotherapy -- Molecular Imaging for the Assessment of Tumor Malignancy and Response to Therapy -- Development of a Prototype 3D PET Scanner Using Semiconductor Detectors and Depth of Interaction Information -- A New PET Scanner with Semiconductor Detector Reveals Intratumoral Inhomogeneous Cell Activity with High Spatial and Energy Resolution -- A New Positron Emission Tomography (PET) Scanner with Semiconductor Detectors for Target Volume Delineation and Radiotherapy Treatment Planning in Patients with Nasopharyngeal Carcinoma -- Initial Performance Measurement of an Integrated PET/SPECT/CT System for Small-Animal Imaging -- Molecular Imaging of Atherosclerotic Plaque Vulnerability: Comparison between 18F-FDG and 99mTc-Annexin A5 -- Quantification of Myocardial Blood Flow Using Rubidium-82 PET -- Molecular Imaging for Regenerative Treatment -- New Concepts for Molecular and Functional Imaging of the Heart: Implications for Regenerative Treatments -- Molecular Imaging of Angiogenesis -- Spontaneous In Vivo Regeneration of the Articular Cartilage Using a Novel Double-Network Hydrogel -- Bone Marrow Stromal Cell Transplantation for Central Nervous System Disorders: Perspectives for Translational Research and Clinical Application -- Noninvasive Optical Tracking of Bone Marrow Stromal Cells Transplanted into Rat Cerebral Infarct -- Thermoreversible Gelation Polymer (TGP) Hydrogel as a Degradable Scaffold for Bone Marrow Stromal Cell Transplantation -- Beneficial Effects of Bone Marrow Stromal Cell Transplantation on Axonal Regeneration in Injured Spinal Cord -- Transplanted Bone Marrow Stromal Cells Improve Cognitive Function after Diffuse Axonal Injury in Rats -- Molecular Imaging and Future Perspectives of Brain Research -- Ultra-High Throughput Screening (uHTS) Chemical Genetics to Identify Novel Chronotherapeutics -- Cell Death and Autophagy -- Bioluminescent Imaging for Assessing Heterogeneous Cell Functions in the Mammalian Central Circadian Clock -- Early Postnatal Stress and the Serotonergic System in the Brain -- Neural Circuit Development and Plasticity Shaped by Glutamate Transporters -- Molecular and Functional Imaging for Drug Development and Elucidation of Disease Mechanisms Using Positron Emission Tomography (PET) -- Recent Trends in Drug Developments -- The Sea as a Source of New Drugs -- PET/AMS Applications in Drug Development -- Functional and Structural Analysis Reveals Dual Function on C-Terminal ? Helix of Alg13 Protein -- Discovery of a First-in-Class Drug, a Prostaglandin D2 Antagonist, for the Treatment of Allergic Diseases -- Towards Developing a Golgi Simulator: Microfluidic Device Enabling Synthesis of a Tetrasaccharide -- An Efficient Strategy for the Exploration of Specific Inhibitors of Sialyltransferases.
Keywords: Medicine; Radiology, Medical; Medicine & Public Health; Imaging / Radiology